2020
DOI: 10.1055/s-0040-1718913
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Repair of Triangular Fibrocartilage Complex Tears: A Systematic Review

Abstract: Objective This study systematically reviews the outcomes of surgical repair of triangular fibrocartilage complex (TFCC) tears. Existing surgical techniques include capsular sutures, suture anchors, and transosseous sutures. However, there is still no consensus as to which is the most reliable method for ulnar-sided peripheral and foveal TFCC tears. Methods A systematic review of MEDLINE and EMBASE was performed according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…This study is designed to evaluate arthroscopic synovectomy for the treatment of rheumatic wrist arthritis. Wrist arthroscopy is a minimally invasive procedure often used by wrist surgeons to diagnose post-traumatic wrist pathology, repair ligament tears and resect ganglion cysts [ 44 46 ]. Earlier studies have demonstrated improvement of wrist function and pain after arthroscopic synovectomy in RA patients [ 17 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study is designed to evaluate arthroscopic synovectomy for the treatment of rheumatic wrist arthritis. Wrist arthroscopy is a minimally invasive procedure often used by wrist surgeons to diagnose post-traumatic wrist pathology, repair ligament tears and resect ganglion cysts [ 44 46 ]. Earlier studies have demonstrated improvement of wrist function and pain after arthroscopic synovectomy in RA patients [ 17 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] However, advances in wrist arthroscopy have allowed for all-arthroscopic repair, with good functional outcomes. 9,10 In line with these results, open repair of TFCC 1B lesions was selected by only 1% of respondents in this survey. Different methods for performing TFCC repair were not included in this survey because of the large number and rapid development of new techniques.…”
Section: Triangular Fibrocartilage Complex Injuriesmentioning
confidence: 99%
“…Recent studies have shown that arthroscopic repair of TFCC injuries leads to good clinical and patient-related outcomes. 9,10 Likewise, improvement of wrist function has been demonstrated following reconstruction of SLL injuries, 11 for which several arthroscopic suturing and anchoring techniques have been described. 6,12,13 The number of published papers in PubMed on the topic of wrist arthroscopy has doubled since 2010 and is now well over 2,000.…”
mentioning
confidence: 99%
“…In the repair methods, pull-out suture showed greater biomechanical resistance in comparison with the anchor technique 3 and overall better functional outcomes were reported using a transosseous suture compared with suture anchors. 19,20 The other important perspective is that the remnants of torn pc fibers usually retract, fibrose, and absorb in chronic cases. Therefore, approximation and maintaining its position by simple suturing cannot guarantee biological healing.…”
mentioning
confidence: 99%